Trato bendito : retórica, teologia e catequese nas cartas dos primeiros jesuítas do estado do Brasil (1549-1553) - Jaime, Iuri Pereira, 1973- (2021)
Orientadores: Marcos Aparecido Lopes, João Adolfo Hansen